Polymer-assisted metal deposition (PAMD) a full-solution strategy for flexible, stretchable, compressible, and wearable metal conductors - Yu, You (Advanced materials (Deerfield Beach, Fla.), 2014)
© 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.